Enhancement of separation selectivity of hemicellulose from bamboo using freeze–thaw-assisted p-toluenesulfonic acid treatment at low acid concentration and high temperature. (November 2022) - Peng, Meijiao; Zhu, Jiatian; Luo, Yadan; Li, Tao; Xia, Xuelian; Qin, Chengrong; Liang, Chen; Bian, Huiyang; Yao, Shuangquan
Graphical abstract: Highlights: Bamboo was separated by freeze–thaw assisted p -toluenesulfonic acid treatment. Separation yield of hemicellulose increased from 60.38% to 93.26%. Separation yield of lignin decreased from 69.29 to 13.98%. Lignin dissolution was inhibited during the efficient hemicellulose separation. Abstract: The cellulose-rich residual solids are obtained with p -toluenesulfonic acid ( p -TsOH) treatment. However, better fractionation of hemicellulose and separation is difficult to obtain during treatment. This study aims at investigating the separation selectivity of bamboo hemicellulose using freeze–thaw-assisted p -TsOH (F/ p -TsOH) treatment. The desired separation effect was achieved at freezing temperature −40 °C, freezing time 20 h, p -TsOH concentration 3.0 %, treatment temperature 130 °C and time 80 min. 93.26 % hemicellulose separation was found, which was 32.88 % higher than that of conventional p -TsOH treatment. Furthermore, the separation yield of lignin decreased significantly from 69.29 % to 13.98 %. The distinct lignin characteristic absorption peaks were found, while that of hemicellulose was difficult to observe. The fiber crystallinity index increased from 50.42 to 56.55 %. Furthermore, greater selectivity for hemicellulose separation was achieved. The results provide a new research thinking for efficient fractionation of lignocellulosic biomass by organic acid treatment.